Constitutional Mixologists: Muddling the Analysis of Protectionist Alcoholic Beverage Laws After Granholm v. Heald - Paul Knettel (Washington University Law Review, 2016)
In its 2005 decision in Granholm v. Heald, the U.S. Supreme Court declared that state alcoholic beverage laws that discriminate against out-of-state entities are unconstitutional restrictions of interstate trade under the dormant Commerce Clause. Despite this holding, lower courts have split in their analyses and conclusions regarding protectionist alcoholic beverage laws. Specifically, the Eighth Circuit recently upheld Missouri’s residency requirements for alcoholic beverage distributors. Meanwhile, a district court in Michigan has found that a similar law imposing residency requirements on alcoholic beverage retailers was an unconstitutional restriction of interstate commerce. This confusion adversely affects both consumers and smaller producers of alcoholic beverages. Therefore, this Note argues the Supreme Court should, in the appropriate case, clarify that Granholm applies to residency requirements for wholesalers and retailers, thereby subjecting these restrictions to heightened Commerce Clause scrutiny.
Keywords: Alcohol laws; Alcohol distributors; Commerce Clause; Dormant Commerce Clause; Business residency requirements; Constitutional Law